Keeping Warm : Urban Heating Options in Tajikistan - Balabanyan, Ani; Hofer, Kathrin; Finn, Johua; Hankinson, Denzel (World Bank, Washington, DC, 2015)
This report identifies the most viable heating options and related investment measures to meet heating demand in urban residential and public buildings in Tajikistan. The report provides an overview of the condition and performance of the urban heating sector and building stock, and assesses, in detail, the situation in Dushanbe and Khujand. The report gives introduction in section one. Section two gives an overview of the physical, institutional, and regulatory characteristics of the urban heating sector in Tajikistan and includes an analysis of the urban building stock. Sections three and four describe the heat supply and demand characteristics of Dushanbe and Khujand and estimate the unmet heating demand in these cities. Section five evaluates the available supply and demand side heating options and investment measures that can be implemented to improve the heating sectors in the target cities. Section six recommends priority investment measures for each building type, identifies related policy actions to facilitate implementation of the recommended investments, highlights key implementation issues, and describes the next steps necessary to implement them.